PROPERTY BUSINESS MANAGEMENT AND MARKETING - Depi Sri Rahayu (CV. ADIBA AISHA AMIRA, 2024)
Property refers to something that is usually known as an entity in relation to the ownership of a person or group of people over an exclusive right. Property Management can be defined as the task of a group of people or organisations with the aim of managing property that is limited to tangible goods owned by individuals or companies in order to achieve predetermined goals. The objectives of property management are as follows: Managing property as a business investment, namely maximising income and investor capital, Managing and implementing physical aspects effectively and efficiently, in order to get optimal results. Marketing is a process and managerial that makes individuals or groups get what they need and want by creating, offering and exchanging products of value to other parties or all activities related to the delivery of products or services from producers to consumers. Marketing management is an effort to plan, implement (which consists of organising, directing, coordinating) and supervising or controlling marketing activities in an organisation in order to achieve organisational goals efficiently and effectively. The main objective of marketing management is the continuity between demand and supply.